A dimensão estética como acolhimento educativo das crianças: uma reflexão sobre o projeto de memórias - Amorim, Carolline (Universidade Federal de São Carlos, 2025)
This undergraduate thesis aims to understand how the aesthetic dimension can foster a sensitive and meaningful educational environment for children at school, drawing inspiration from the principles of Reggio Emilia. The research is also based on the contributions of Stella Barbiero and Gianfranco Staccioli, who deepen the understanding of the role of aesthetics, environments, and the multiple languages of childhood in daily school life. Starting from the concept of the child as a protagonist and competent individual, the importance of active listening and a sensitive observation by the teacher towards children's expressions is discussed. The study articulates the theoretical frameworks with the experiences conducted by the author with classes in Early Childhood Education and Elementary School I, composed of children aged 4, 5, 6, and 7 years old, highlighting how spaces, pedagogical documentation, and children's productions transform the school environment into a living, expressive place that belongs to them. The research is based on a qualitative approach, of a bibliographic nature, with reflections on the author's field experiences. It is concluded that aesthetics, understood as a sensitive and relational experience, combined with the arts and the careful preparation of environments, contributes to children feeling welcomed and recognized as integral and very important members of the school community.
The aesthetic dimension as educational welcoming for children: a reflection on the memory project
Keywords: Estética; Aesthetics; Acolhimento; Welcoming; Educação infantil; Early childhood education; Escuta ativa; Active listening; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade